Hysteroscopy needs of indigenous communities in Northern Quebec: a retrospective cohort study - Andrew Zakhari; Dong Bach Nguyen; Jessica Papillon Smith; Fady W. Mansour; Srinivasan Krishnamurthy (International Journal of Circumpolar Health)
We aimed to determine the surgical output for patients from Nunavik undergoing transfer to an urban centre for hysteroscopy, and associated costs. We performed a retrospective chart review of all patients from the 14 villages of Nunavik transferred for hysteroscopic surgery from 2016 to 2021. Diagnoses, surgical intervention, and nature of the procedure were all extracted from the patient charts, and costs/length of stay obtained from logisticians and administrators servicing the Nunavik region. Over a 5-year period, 22 patients were transferred from Nunavik for hysteroscopy, of which all were elective save one. The most common diagnosis was endometrial or cervical polyp and the most common procedure was diagnostic hysteroscopy. The average cost for patient transfer and lodging to undergo hysteroscopy in Montreal ranged from $6,000 to $15,000 CDN. On average, 4–5 patient transfers occur annually for hysteroscopy, most commonly for management of endometrial polyps, at a cost of $6,000 to $15,000 CDN, suggesting the need to investigate local capacity building in Nunavik and assess cost-effectiveness.